A drug safety evaluation of rituximab and risk of hepatitis B. (July 2014) - Riedell, Peter; Carson, Kenneth R
<x xml:space="preserve">Abstract</x> Introduction: <ext-link ext-link-type="uri" xlink:href="http://informahealthcare.com/action/doSearch?type=advanced&displaySummary=true&displaySummary=true&field1=keywords&text1=Rituximab&logicalOpe1=OR&field2=articletitle&text2=Rituximab&logicalOpe2=AND&field3=all&text3=&search=Search&categoryId=41010274&categoryId=40002416&categoryId=40004717&categoryId=40004717&filter=multiple&AfterMonth=1&AfterYear=&BeforeMonth=12&BeforeYear=&sortBy=date&nh=20" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink"> Rituximab is a widely prescribed anti-CD20 mAb for the treatment of CD20+ B-cell non-Hodgkin Lymphoma and many other immune mediated conditions. There is a well-described association between rituximab containing chemo-immunotherapy treatment and reactivation of the hepatitis B virus (HBV). This review summarizes the current literature surrounding rituximab-associated HBV reactivation. Areas covered: Herein, we review the literature detailing the risk of HBV reactivation in inactive carriers and those with resolved hepatitis. The clinical presentation and management of HBV reactivation are also discussed along with a summary of clinical trials evaluating antiviral prophylaxis. Finally, clinical recommendations are detailed. Data from clinical trials, observational studies, reviews, and meta-analyses available in the Medline database were included in this narrative review. Expert opinion: Screening should be performed in all patients prior to the administration of any type of anti-CD20 mAb therapy. Among those with positive screening serology, testing for hepatitis B e antigen or viral load by polymerase chain reaction is appropriate. In those patients with detectable HBV DNA, the decision regarding the use of antiviral prophylaxis or observation should be individualized.